A Note on the Tail Behavior of Randomly Weighted Sums with Convolution-Equivalently Distributed Random Variables - Yang Yang; Jun-feng Liu; Yu-lin Zhang (Abstract and Applied Analysis)
We investigate the tailed asymptotic behavior of the randomly weighted sums with increments with convolution-equivalent distributions. Our obtained result can be directly applied to a discrete-time insurance risk model with insurance and financial risks and derive the asymptotics for the finite-time probability of the above risk model.